4+3p-1=7p+10-3p

Simple and best practice solution for 4+3p-1=7p+10-3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3p-1=7p+10-3p equation:


Simplifying
4 + 3p + -1 = 7p + 10 + -3p

Reorder the terms:
4 + -1 + 3p = 7p + 10 + -3p

Combine like terms: 4 + -1 = 3
3 + 3p = 7p + 10 + -3p

Reorder the terms:
3 + 3p = 10 + 7p + -3p

Combine like terms: 7p + -3p = 4p
3 + 3p = 10 + 4p

Solving
3 + 3p = 10 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
3 + 3p + -4p = 10 + 4p + -4p

Combine like terms: 3p + -4p = -1p
3 + -1p = 10 + 4p + -4p

Combine like terms: 4p + -4p = 0
3 + -1p = 10 + 0
3 + -1p = 10

Add '-3' to each side of the equation.
3 + -3 + -1p = 10 + -3

Combine like terms: 3 + -3 = 0
0 + -1p = 10 + -3
-1p = 10 + -3

Combine like terms: 10 + -3 = 7
-1p = 7

Divide each side by '-1'.
p = -7

Simplifying
p = -7

See similar equations:

| Cos40=X/6 | | 2u-0.75u+5=105 | | x+2.5y=450 | | 2(4n-7)=4n-18 | | 9r-6r+7=7r+7-r | | (4n^2)+12n=-9 | | x+5/x-5= | | 5w(-3w^2+2w-4)= | | -13x-12=9-6x | | 185x+(7624)=-12790 | | 21+5x=7x-179 | | (w-4)(w+1)= | | (16x-4)=(4-4x) | | 26-7x=89 | | f(x)=-2x^2+6x-4 | | (w^2-2w-7)+(3w^2-5w+4)= | | f(1)=2x^2+7x+3 | | (2x^2)-6x=-4 | | 5t+3=8-2t | | 4r+3s+2r=6r+3s | | 7.5(w-2.5)=1.5(3-2w) | | 4x^2-x=-9x | | 13m-27=9m-6 | | -4x-20= | | I=0.4/5 | | 24=X-24 | | (14-2x)(8-2x)=40 | | (x^2)+2t-5=19 | | 7(6y-5(4y-11))=7-8y | | (8x+7)(8x+7)(4x+3)(x+1)=15 | | 3(15x)+7y=208 | | -X-17=3x-1 |

Equations solver categories